48 Expression pattern and significance of homeodomain only protein (HOPX) in head and neck cancer. Issue 5 (May 2015) - ,; Paterson, I.C.
Abstract : Background: The homeodomain only protein, HOPX (also known as HOP, NECC1, LAGY or OB1) was initially identified as a gene essential for cardiac development. HOPX is unusual because although it forms a classical homeodomain fold it lacks DNA-binding capacity due to the absence of several key residues known to mediate critical contacts with DNA that are conserved among other homeodomain proteins. The aim of this study is to investigate the expression pattern and role of HOPX in head and neck cancer. Methods: Immunohistochemistry, Reverse Transcriptase-PCR and QPCR were performed to study the expression pattern of HOPX in head and neck carcinoma tissues and cell line. In addition, MTT, Transwell migration, Annexin V/PI staining for apoptosis and colony forming assay have been used to investigate the effect of forced HOPX expression in head and neck carcinoma cells. Results: HOPX expression is markedly reduced in head and neck carcinoma tissues and cell line when compared with normal epithelial cells. Interestingly, forced expression of HOPX reduces plating efficiency, migration and sensitizes carcinoma cell to UV induced apoptosis. Conclusion: Our results demonstrate that the loss of HOPX leads to more aggressive phenotype and insists the need to investigate the precise role of HOPX in homeostasis and tumor progressive for therapeutic implication.